A pesquisa participante na elaboração de atlas escolar: a experiência do atlas de Apucarana - PR - Faria, Maria do Carmo Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Geography, as an area of knowledge, takes part in the great challenge that is building an idea of space. In teaching Geography, the cartographic representation enables students to elaborate knowledge about the space where they and other social subjects live. This research mainly aims to present the experience of elaborating a Municipal School Atlas for Apucarana, a municipality within the state of Paraná in the South of Brazil. The Atlas highlights historic, geographic and environmental aspects and is based upon a participatory research. Teachers who worked on the municipal teaching system took part in the research, and to do so, a study group was formed by the researcher and primary school teachers from the municipality in order to develop and evaluate the applicability of the Atlas. Our work was guided by a suggestion by Freire (1984), who outlined a research project towards education, specifically the education of adults in Tanzania. This methodology suggests that the researcher engages with popular classes in order to conduct a research, which happened in our case through the study group with the teachers. In the meetings, we conducted studies concerning our training, we applied the activities related to geography topics in the classroom, and we applied the activities from the prototype of the Atlas. We were also able to verify the relevance of the pages in the prototype and to suggest new pages for the Atlas. In addition to performing a literature review in order to verify the methodological principles of the participatory research, we conducted a survey of existing Municipal School Atlas in Brazil from 1959 to 2013 and a survey of the situation of School Cartography in Brazil from the first Cartography Conference for Children in 1995 until the most recent one, the seventh Cartography Conference for Children in 2013. An Atlas which takes into account the view of researcher, teachers and students was the result of this research, as ...

A Geografia, como uma área do conhecimento, tem o grande desafio de auxiliar na construção da ideia de espaço. A representação cartográfica, por meio do ensino da Geografia, proporciona ao estudante a elaboração de saberes sobre os lugares onde ele e outros sujeitos sociais vivem. Esta pesquisa tem como objetivo central apresentar a experiência de elaboração do Atlas Municipal Escolar para o município de Apucarana-PR, destacando aspectos históricos, geográficos, e ambientais, apoiada na Pesquisa Participante. Essa pesquisa ocorreu com a participação de professoras que trabalhavam na rede municipal de ensino. Para tanto, formamos um grupo de estudos composto pela pesquisadora e por professoras do Ensino Fundamental I do município para desenvolver e avaliar a aplicabilidade do Atlas. Pautamos nosso trabalho em uma sugestão de Freire (1984). O autor traça um projeto de pesquisa direcionado para a educação, especificamente para a Educação de Adultos na Tanzânia. Essa metodologia propõe que o pesquisador se engaje às classes populares para a realização da pesquisa, o que ocorreu no nosso caso através do grupo de estudos com as professoras. Nesse grupo, realizamos estudos para nossa formação, aplicamos em sala de aula atividades referentes a assuntos geográficos, aplicamos também as páginas do protótipo e as páginas do Atlas; pudemos ainda verificar a pertinência das páginas organizadas no protótipo e sugerir novas paginas para compor o Atlas. Além de realizarmos um levantamento bibliográfico para verificarmos os princípios metodológicos da Pesquisa Participante; realizamos um levantamento dos Atlas Municipais Escolares publicados no Brasil de 1959 a 2013; e fizemos um levantamento de como está a Cartografia Escolar no Brasil desde o seu primeiro Colóquio de Cartografia para Crianças em 1995 até o mais recente ocorrido, o VIII Colóquio de Cartografia para Crianças no ano de 2013. O resultado dessa...
Keywords: Cartography; Geografia - Estudo e ensino; Professores de geografia; Cartografia; Apucarana (PR) - Atlas